(untitled) (Південний архів (історичні науки), 2024)
The porpouse of this articleis to examine and analyze the main stages of the formation and development of youth groups at the communities of Evangelical Christians and Baptists in Galicia and Volyn in the interwar decades. Based on general and specific historical methods such as analisise, comperative and chronological methods the main activities of youth circles are identified, and their active participation in the missionary activities of the movement in these territories is proved. As a results the educational and upbringing activities of the circles are highlighted. Also, their influence on the formation of the theological agenda in the associations of Evangelical Christians and Baptists in the interwar decades is analyzed. Conclusions.Summarizing the review of the history of the development and activity of youth groups at the EHB communities, we can say that youth groups, as an element of the religious and worldview educational process in the middle of the communities, were an important element of their institutional and confessional formation. Youth circles have gone through a rather dynamic path from the establishment of single and unrelated separate structural units at communities to a well-organized administrative and management network of circles with a developed management, educational and missionary network. Despite the theological affinity between evangelical Christianity and baptism, already in the 20s of the 20th century. the process of gradually creating two independent verticals of youth group management at the communities of both currents began. Institutionally, this process was completed in 1935 with the promulgation of the Statute of Evangelical Youth Circles under evangelical christian communities. Youth groups that operated under Baptist communities, although during the interwar decades and remained part of the same management network, still formed separate national structures, as, for example, Baptist youth in Galicia did. On the contrary, the youth groups operating under EC communities tried in every possible way to preserve their supranational status, uniting in their ranks representatives of various nationalities who belonged to this Protestant trend. The structural organization of circles into separate unions and associations contributed to the intensification of the missionary activity of youth in communities, which in turn made it possible to increase the number of supporters of both currents and establish intra-church work with youth within the movement itself.